Sovereign credit ratings and the transnationalization of finance: Evidence from a gravity model of portfolio investment - Finn Marten Körner; Hans-Michael Trautwein (Kiel Institute for the World Economy (IfW), 2014)
It is a matter of debate in how far credit ratings contribute to allocative efficiency or to excessive volatility of asset prices and cross-border capital flows. Yet it is generally taken for granted that ratings play a significant role in the transnationalization of financial relations. This paper tests the hypothesis with regard to data on sovereign credit ratings and foreign portfolio investment. A rating-related gravity model of finance is derived from the choice-theoretical framework of Okawa and van Wincoop (Gravity in International Finance, 2012) and estimated in three stages. At the first stage, the authors find that the introduction and evolution of sovereign ratings and their gradual improvement since the 1970s has affected inward portfolio investment stocks and flows in host countries. At the second stage, the authors examine to which extent sovereign ratings help to predict the degree of investors' home bias, as measured by the share of outward portfolio investment holdings in the home countries' portfolios, and whether they can account for the divergent dynamics before and after the global financial crisis. At the third stage, the authors look at the explanatory content of ratings for the determination of the size of bilateral portfolio investment. Evidence for a significant role of sovereign ratings is found at all three stages.
Keywords: F41; F65; G11; G24; 330; credit rating agencies; portfolio investment; gravity model; home bias